Atlantic forest replacement by non native tree plantations : comparing aboveground necromass between native forest and pine plantation ecosystems - Zaninovich, Silvia Clarisa (2016)
Fil: Zaninovich, Silvia Clarisa. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad Nacional de Misiones. Instituto de Biología Subtropical; Argentina.